Model Pembelajaran Passing Bawah Sepakbola Dengan Menggunakan 1, 2 Dan 3 Bola - Jack Suman Rulis Manurung; Siskariyanti Siskariyanti (Jurnal MensSana, 2021)
This research is based on the problem of the limitations of the ball in football learning. The most important thing in learning football is the presence of a ball to carry out the learning of football. This study aims to create a learning model of football passing under using limited media. The model trial was carried out in 2 stages with small groups and large groups. The small group used 15 students and the large group used 80 students, where the students who were the sample were STKIP Pamane Talino students. Because it is still the covid 19 period, the trial was carried out with health protocols and did not use a sample that was too wide considering the impact that could occur. This exercise model has three stages of movement that become an integral part of this learning model. The three stages of the movement, namely initial motion, core motion and final motion, each stage has a variation of the movement model. Testing the effectiveness of the model created by providing a questionnaire on student responses to learning with the old model and the new model created. Based on the responses given by the new football passing learning model, it makes students easy in the learning process, minimizes boredom, students feel more tired because they move a lot and foster feelings of pleasure in learning.